Mechanisms of Antimicrobial Peptides from Bagasse against Human Pathogenic Bacteria - Thitiporn Ditsawanon; Narumon Phaonakrob; Sittiruk Roytrakul (MDPI AG, 2023)
Nonedible agricultural wastes (agricultural wastes, agro-industrial wastes, and fishery wastes) were chosen as potential sources of antimicrobial peptides and evaluated for antibacterial efficiency against human pathogens. Specifically, protein hydrolysates were first obtained by hydrolysis with pepsin. Filtrated peptides smaller than 3 kDa were then purified by C18 reversed-phase chromatography, cation exchange chromatography, and off-gel fractionation. NanoLC-MS/MS was used to investigate the amino acid sequences of active peptide candidates. Five candidate peptides were finally chosen for chemical synthesis and evaluation of growth inhibition against human pathogenic bacteria. Two synthetic peptides from bagasse, NLWSNEINQDMAEF (Asn-Leu-Trp-Ser-Asn-Glu-Ile-Asn-Gln-Asp-Met-Ala-Glu-Phe) and VSNCL (Val-Ser-Asn-Cys-Leu), showed the most potent antibacterial activity against three pathogens: Pseudomonas aeruginosa, Bacillus subtilis, and Burkholderia cepacia. The antibacterial mechanisms of these peptides were then examined using shotgun proteomics, which revealed their effects to involve both intracellular-active and membrane-active mechanisms. Further investigation and modification of peptides are needed to increase the efficiency of these peptides against human pathogens.